The impact of HLA-DRB1 genes on extra-articular disease manifestations in rheumatoid arthritis - Turesson, Carl (BioMed Central, 2005)
The objective of this study was to examine HLA-DRB1 and HLA-DQB1 genotypes in patients with severe extra-articular rheumatoid arthritis (ExRA) and to compare them with the genotypes of rheumatoid arthritis (RA) patients without extra-articular manifestations. Patients with severe ExRA were recruited from a large research database of patients with RA, from two cohorts of prevalent RA cases, and from a regional multicenter early RA cohort. Cases with ExRA manifestations (n = 159) were classified according to predefined criteria. Controls (n = 178) with RA but no ExRA were selected from the same sources. Cases and controls were matched for duration of RA and for clinical center. PCR based HLA-DRB1 and HLA-DQB1 genotyping was performed using the Biotest SSP kit, with additional sequencing in order to distinguish DRB1*04 subtypes. Associations between alleles and disease phenotypes were tested using multiple simulations of random distributions of alleles. There was no difference in global distribution of HLA-DRB1 and HLA-DQB1 alleles between patients with ExRA and controls. DRB1*0401 (P = 0.003) and 0401/0401 homozygosity (P = 0.002) were more frequent in Felty's syndrome than in controls. The presence of two HLA-DRB1*04 alleles encoding the shared epitope (SE) was associated with ExRA (overall odds ratio 1.79, 95% confidence interval 1.04–3.08) and with rheumatoid vasculitis (odds ratio 2.44, 95% confidence interval 1.22–4.89). In this large sample of patients with ExRA, Felty's syndrome was the only manifestation that was clearly associated with HLA-DRB1*0401. Other ExRA manifestations were not associated with individual alleles but with DRB1*04 SE double dose genotypes. This confirms that SE genes contribute to RA disease severity and ExRA. Other genetic and environmental factors may have a more specific impact on individual ExRA manifestations.